Recent Advances in FDTD Modeling of Electromagnetic Wave Propagation in the Ionosphere - Nguyen, Bach T.; Samimi, Alireza; Simpson, Jamesina J. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Finite-Difference Time-Domain (FDTD) modeling of electromagnetic wave propagation in the Earth-ionosphere waveguide has gained significant interest over the past two decades. Initially, FDTD modeling capabilities were largely limited to two-dimensional models assuming a plasma ionosphere (but incapable of accounting for Faraday rotation), or to threedimensional global models assuming a simple, isotropic conductivity profile ionosphere. Two algorithm developments have recently advanced the state-of-the-art in electromagnetic wave calculation capabilities in the ionosphere: (1) A new, three-dimensional efficient FDTD magnetized plasma model. (2) A Stochastic FDTD (S-FDTD) model of magnetized ionospheric plasma. The first capability permits longer-distance, higher frequency and higher altitude propagation studies by greatly reducing the memory requirements and simulation time relative to previous plasma models. The second capability introduces for the first time a way of solving for not only mean electromagnetic field values, but also their variance. This paper provides an overview of these two recent advances.